Elastic acrylic emulsion with coating structure and application of elastic acrylic emulsion in water-based damping coating

By developing an elastic acrylic emulsion with a coated structure, the problems of water-based damping coatings bubble, cracking and insufficient adhesion under high-temperature baking conditions are solved, and higher damping values, wider temperature domains and good adhesion are achieved.

CN119899329APending Publication Date: 2025-04-29SHENYANG PARKERIZING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510034291.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing water-based damping coatings are prone to foaming and cracking under high-temperature baking conditions, and lack adhesion, especially in humid and hot conditions.

Method used

An elastic acrylic emulsion with a coated structure is developed, and the modified cellulose is embedded through the combination of coated particles and three-layer cladding layers to form an inner and outer layer structure, thereby improving the high temperature baking resistance and adhesion of the coating.

Benefits of technology

It is achieved to avoid the paint bubbles and cracks under high-temperature baking conditions, improve the damping value and temperature range, and improve the adhesion of the substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235100240000041
    Figure BDA0005235100240000041
  • Figure BDA0005235100240000051
    Figure BDA0005235100240000051
  • Figure BDA0005235100240000052
    Figure BDA0005235100240000052
Patent Text Reader

Abstract

The invention relates to the field of damping coatings, in particular to an elastic acrylic emulsion with a coating structure and application of the elastic acrylic emulsion in a water-based damping coating. The synthesis method comprises the following steps: firstly, polymerizing a first monomer with a silane coupling agent, an emulsifier and an initiator to obtain coated particles with Tg of 35-45 DEG C; then, three coating layers are grafted on the coated particles, the Tg of the three coating layers is sequentially reduced, and the modified cellulose is embedded, so that the elastic acrylic emulsion with the coating structure is obtained. In the coating layer, the functional modified cellulose is polymerized onto a molecular chain, so that the surface of the particle is endowed with extremely strong water-retaining property. The special structure enables the internal cross-linking of the particles to be compact, the outer layers of the particles to be elastic and soft, the gaps among the particles are larger, and relative sliding is easier. When being applied to a damping coating, the coating can solve the problems of blistering and cracking during high-temperature baking and drying; and meanwhile, the coating has the excellent characteristics of higher damping value, wider temperature range and good adhesive force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of damping coatings, and in particular to an elastic acrylic emulsion with a coating structure and application thereof in water-based damping coatings. Background Art

[0002] In recent years, with the rapid development of my country's automobile industry and the continuous increase in automobile production, automobile manufacturers and OEMs have higher requirements for environmental friendliness and sustainable development. As a water-based damping coating for shock and noise reduction, it has gradually entered the public's field of vision. The simple construction spraying method is also one of the reasons why it can quickly replace traditional asphalt sheets and achieve rapid development.

[0003] At present, the damping coating still has the following problems in the technical field: 1) Excessive focus on construction performance, unable to further improve or balance the damping characteristics. Since the water-based damping coating must enter a drying oven at about 150°C after being sprayed on the car body and quickly dry within 20 minutes, if the coating has poor high-temperature baking resistance, the surface will dry quickly and the internal moisture cannot evaporate, causing bubbling and cracking. For this reason, a large number of raw material manufacturers have listed the problem of high-temperature baking without bubbling and cracking as a top priority, ignoring the improvement of damping characteristics. This can be reflected in a large number of patents. 2) The adhesion to the substrate electrophoretic paint is low, especially when the car is in hot and humid conditions for a long time, the risk of shedding increases. In the damping coating system, acrylic emulsion plays a vital role.

[0004] Therefore, it is necessary to develop an acrylic emulsion that has the characteristics of high temperature baking resistance, high damping, wide temperature range, and good adhesion. Summary of the invention

[0005] In order to overcome the above problems, the present invention provides an elastic acrylic emulsion with a coating structure and an application method thereof in a damping coating, which solves the problem of blistering of high-temperature baking coatings and has high-quality characteristics such as higher damping value, wider temperature range and good adhesion.

[0006] To achieve the above object, an elastic acrylic emulsion with a coating structure is prepared by a synthesis method comprising the following steps:

[0007] 1) Firstly, a first monomer is polymerized with a silane coupling agent, an emulsifier, and an initiator to obtain coated particles having a Tg of 35 to 45° C.;

[0008] 2) Then three coating layers are grafted onto the coated particles, the Tg of the three coating layers decreases in sequence, and modified cellulose is embedded, so as to obtain a coated structure elastic acrylic emulsion.

[0009] In the above elastic acrylic emulsion with a coating structure, in step 1), the first monomer comprises: one or more of n-butyl acrylate, isobutyl acrylate, isooctyl acrylate, lauryl acrylate, methyl methacrylate, and styrene.

[0010] In the above elastic acrylic emulsion with a coating structure, in step 1), the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the amount used is 0.1-1% of the total weight of the formula.

[0011] In the above-mentioned elastic acrylic emulsion with a coating structure, in step 1), the emulsifier is one or more of sodium alkyl sulfosuccinate A102, sodium salt of alkylphenol ether sulfosuccinate MS-1, and castor oil polyoxyethylene ether EL-10; and the initiator is one of persulfate, ammonium persulfate, sodium persulfate, and potassium persulfate.

[0012] The above-mentioned elastic acrylic emulsion with a coating structure, the monomers used to synthesize the three coating layers include: one or more of n-butyl acrylate, isooctyl acrylate, and methyl methacrylate.

[0013] The elastic acrylic emulsion with a coating structure mentioned above has three coating layers whose Tgs are 15 to 25°C, -5 to 5°C, and -25 to -15°C respectively.

[0014] In the above-mentioned elastic acrylic emulsion with a coating structure, the weight ratio of the coated particles to the monomers used in the three coating layers is 2:1:1:1.

[0015] The above-mentioned elastic acrylic emulsion with a coating structure, the modified cellulose preparation method comprises the following steps:

[0016] First, 90-100 parts of cellulose and 180-200 parts of ethyl acetate are mixed by mass, and stirred for 1-2 hours. Then, 40-50 parts of pyrrole are gradually added dropwise to the system, and stirring is continued for 30-40 minutes after the addition. Then, 90-100 parts of acrylic acid are added dropwise, and the reaction is carried out for 30-40 minutes. Finally, anhydrous ethanol is added for washing, and the mixture is filtered and dried to obtain modified cellulose with a double bond structure.

[0017] The modified cellulose in the elastic acrylic emulsion with a coating structure is acrylic acid-modified cellulose, and the amount used is 1-2% by weight of the total formula.

[0018] The elastic acrylic emulsion with a coating structure is used in the preparation of damping coatings. The formulated amount of water, the elastic acrylic emulsion with a coating structure, additives and fillers are stirred evenly, dispersed at high speed and the viscosity is adjusted.

[0019] Compared with the prior art, the present invention is beneficial in that:

[0020] The acrylic emulsion of the invention is composed of coated particles and three coating layers. The coated particles are internally cross-linked, so that the material has good adhesion to the substrate.

[0021] Modified cellulose is polymerized and embedded in the acrylic emulsion coating layer of the present invention, and the outer coating layer has a higher content of modified cellulose. This makes the inner layer of the particle hydrophobic and the outer layer water-retaining, which is more conducive to the rapid release of water vapor from the inside to the outside during the film-forming process under heat, thereby meeting the high-temperature baking conditions and avoiding bubbling, expansion and cracking on the coating surface.

[0022] The acrylic emulsion described in the present invention is an elastic acrylic emulsion with a coating structure. The elastic acrylic emulsion is hard inside and soft outside. When vibration acts on the surface of the material, it is easy for particles to slide, and the inside of the particles can play a supporting role. The outer layer quickly converts mechanical energy into internal energy through elastic deformation to provide greater damping characteristics.

[0023] The present invention uses coating technology to make a particle have four different glass transition temperatures Tg, and can show good damping in different temperature ranges, and has a wide temperature range characteristic.

[0024] The coated structural elastic acrylic emulsion developed by the present invention can solve the problem of blistering of high-temperature baking paint, has a higher damping value, a wider temperature range, and has the high-quality characteristics of integrating good adhesion. DETAILED DESCRIPTION

[0025] The present invention is described in detail below with reference to the embodiments.

[0026] Example 1

[0027] 1. Preparation of modified cellulose:

[0028] First, 100 parts of cellulose and 200 parts of ethyl acetate were mixed by mass and stirred for 2 hours, then 50 parts of pyrrole were gradually added to the system, and stirring was continued for 40 minutes after the addition, and then 100 parts of acrylic acid were added, and the reaction was carried out for 30 minutes. Finally, anhydrous ethanol was added for washing, and the mixture was filtered and dried to obtain a modified cellulose with a double bond structure that can be copolymerized with other acrylic ester monomers.

[0029] 2. Preparation of elastic acrylic emulsion for coating structure:

[0030] Deionized water (50 g) and sodium alkyl sulfosuccinate (2 g) were added into a stirred reactor and heated;

[0031] Coated particle part: Deionized water (17 g), sodium alkyl sulfosuccinate A102 (0.8 g), n-butyl acrylate BA (11 g), methyl methacrylate MMA (29 g), and γ-methacryloxypropyltrimethoxysilane (0.95 g) were mixed and prepared; when the temperature of the reactor was 83° C., the coated particle part and ammonium persulfate initiator (0.26 g) were simultaneously dripped into the reactor within 1 hour, and then kept warm for 10 minutes;

[0032] A coating layer: on the basis of the coated particles, deionized water (8g), sodium alkyl sulfosuccinate A102 (0.3g), n-butyl acrylate BA (7.8g), methyl methacrylate MMA (12.2g), and modified cellulose (0.2g) were mixed and prepared, and ammonium persulfate initiator (0.12g) was added. It was added dropwise to the reactor over 20 minutes and kept warm at 80-86°C for 10 minutes;

[0033] Second layer coating part: on the basis of the first layer of coated particles, deionized water (7g), sodium alkyl sulfosuccinate A102 (0.3g), BA (10.4g), MMA (9.6g), modified cellulose (0.4g) were mixed and prepared, and ammonium persulfate initiator (0.1g) was added. It was added dropwise to the reactor over 20 minutes and kept warm at 80-86°C for 10 minutes;

[0034] Three-layer coating part: on the basis of the two-layer coated particles, deionized water (7g), sodium alkyl sulfosuccinate A102 (0.3g), BA (7.5g), EHA (5g), MMA (7.5g), modified cellulose (0.8g) were mixed and prepared, and ammonium persulfate initiator (0.06g) was added. It was added dropwise to the reactor over 20 minutes and kept at 80-86°C for 1 hour;

[0035] The temperature was lowered to 40°C, and ammonia water was added to neutralize the mixture to a pH of 8 to 9 to obtain an elastic acrylic emulsion with a coating structure.

[0036] Embodiment 2-6

[0037] The same method as in Example 1 was adopted to prepare acrylic emulsion by changing the amount and type of the raw materials for preparing acrylic emulsion as shown in Table 1.

[0038] Comparative Examples 1-7

[0039] The same method as in Example 1 was adopted to prepare acrylic emulsion by changing the amount and type of the raw materials for preparing acrylic emulsion as shown in Table 1.

[0040] Table 1 Amount (g) and type of synthetic emulsion raw materials in the examples and comparative examples

[0041]

[0042] Note:

[0043] For the coated particles in Examples 2-6 and Comparative Examples 1-7, the amount of deionized water added was 17 g, the amount of sodium alkyl sulfosuccinate A102 added was 0.8 g, and the amount of ammonium persulfate initiator added was 0.26 g.

[0044] In the coating part of Example 2-6 and Comparative Example 1-7, the amount of deionized water added was 8 g, the amount of sodium alkyl ether sulfosuccinate A102 added was 0.3 g, and the amount of ammonium persulfate initiator added was 0.12 g.

[0045] In the second-layer coating part of Examples 2-6 and Comparative Examples 1-7, the amount of deionized water added was 7 g, the amount of sodium alkyl sulfosuccinate A102 added was 0.3 g, and the amount of ammonium persulfate initiator added was 0.1 g.

[0046] In the three-layer coating part of Examples 2-6 and Comparative Examples 1-7, the amount of deionized water added was 7 g, the amount of sodium alkyl sulfosuccinate A102 added was 0.3 g, and the amount of ammonium persulfate initiator added was 0.06 g.

[0047] Example 7

[0048] The water-based damping coating was prepared according to the formula shown in Table 2.

[0049] Place the formula water and emulsion in a container and start stirring. Add additives, fillers and other raw materials. After all are added, stir evenly, disperse at high speed and adjust the viscosity.

[0050] Table 2 Water-based damping coating formula

[0051]

[0052] High temperature baking blistering performance test of water-based damping coating: Apply the water-based damping coating to the surface of the electrophoretic paint plate with a thickness of 3mm, and directly bake the sample at 150℃ for 20 minutes to cure, and observe the cracking and blistering of the coating film.

[0053] Adhesion test of water-based damping coating: Apply a film evenly on the test plate with a wedge-shaped applicator, bake at 140℃ for 20 minutes to cure, and cure at room temperature for 24 hours to make a test piece. Make two parallel cuts on the test piece, peel it off from the thinner end to the thicker end by hand, and evaluate it according to the following grades:

[0054] Grade 0 = Excellent, 100% of the material remains on the substrate

[0055] Grade 1 = Good, 90% of the material remains on the substrate

[0056] Grade 2 = Good, material partially remains on substrate

[0057] Grade 3 = Good, all material detached, no adhesion

[0058] Table 3 High temperature baking conditions, adhesion level and damping performance of water-based damping coatings

[0059]

[0060]

[0061] Damping test of water-based damping coating: Damping test is carried out in accordance with GB / T 18258-2000 "Test method for damping performance of damping materials". Standard sample preparation: cold-rolled plate 220mm×10mm×1.0mm, coating size 200mm×10mm×3.0mm. Curing conditions: baking at 140℃ for 20min, and the damping value is obtained by testing with the damping test system.

[0062] Table 4: Damping properties of water-based damping coatings

[0063]

[0064] The results in Table 3 and Table 4 show that Examples 1-6 can simultaneously meet the characteristics of high temperature baking performance, excellent adhesion, high damping, and a wide temperature range, and can adjust the temperature range according to the coating structure to obtain an acrylic emulsion that meets customer requirements.

[0065] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited by the above embodiments. Any modification, replacement and improvement based on the present invention are within the protection scope of this patent.

Claims

1. An elastic acrylic emulsion with a coating structure, characterized in that: The synthesis method comprises the following steps: 1) Firstly, a first monomer is polymerized with a silane coupling agent, an emulsifier, and an initiator to obtain coated particles having a Tg of 35 to 45° C.; 2) Then three coating layers are grafted onto the coated particles, the Tg of the three coating layers decreases in sequence, and modified cellulose is embedded, so as to obtain a coated structure elastic acrylic emulsion.

2. The elastic acrylic emulsion with a coating structure according to claim 1, characterized in that: In step 1), the first monomer includes: one or more of n-butyl acrylate, isobutyl acrylate, isooctyl acrylate, lauryl acrylate, methyl methacrylate, and styrene.

3. The elastic acrylic emulsion with a coating structure according to claim 1, characterized in that: In step 1), the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the amount used is 0.1-1% of the total weight of the formula.

4. The elastic acrylic emulsion with a coating structure according to claim 1, characterized in that: In step 1), the emulsifier is one or more of alkyl alcohol ether sodium sulfosuccinate A102, alkylphenol ether sodium sulfosuccinate MS-1, and castor oil polyoxyethylene ether EL-10; the initiator is one of persulfate, ammonium persulfate, sodium persulfate, and potassium persulfate.

5. The elastic acrylic emulsion with a coating structure according to claim 1, characterized in that: The monomers used to synthesize the three-layer coating layer include: one or more of n-butyl acrylate, isooctyl acrylate, and methyl methacrylate.

6. The elastic acrylic emulsion with a coating structure according to claim 1, characterized in that: The Tg of each layer of the three coating layers is 15 to 25°C, -5 to 5°C, and -25 to -15°C, respectively.

7. The elastic acrylic emulsion with a coating structure according to claim 1, characterized in that: The weight ratio of the coated particles to the monomers used in the three coating layers is 2:1:1:

1.

8. The elastic acrylic emulsion with a coating structure according to claim 1, characterized in that: The modified cellulose preparation method comprises the following steps: First, 90-100 parts of cellulose and 180-200 parts of ethyl acetate are mixed by mass, and stirred for 1-2 hours. Then, 40-50 parts of pyrrole are gradually added dropwise to the system, and stirring is continued for 30-40 minutes after the addition. Then, 90-100 parts of acrylic acid are added dropwise, and the reaction is carried out for 30-40 minutes. Finally, anhydrous ethanol is added for washing, and the mixture is filtered and dried to obtain modified cellulose with a double bond structure.

9. The elastic acrylic emulsion with a coating structure according to claim 8, characterized in that: The modified cellulose is acrylic acid modified cellulose, and the amount used is 1-2% by weight of the total formula.

10. Use of the elastic acrylic emulsion with a coating structure according to any one of claims 1 to 9 in the preparation of a damping coating, characterized in that: The water in a formula amount, the elastic acrylic emulsion with a coating structure according to any one of claims 1 to 9, the auxiliary agent and the filler are stirred evenly, dispersed at a high speed and the viscosity is adjusted.